Swot Analysis To Get Bappeda Strategies In Implementing Planning Services Quality Regional Development In Payakumbuh City - Sistesya, Dilla; Gelvi, Gelvi; Hanifeliza, Rury; Heikal, Jerry (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
This study aims to determine the appropriate strategy used by Bappeda in implementing regional development planning services. The method used in this study is a qualitative research method with a grounded theory approach as a research model. Data collection was carried out by researchers by conducting semi-structured interviews, field observations, document analysis and literature studies. By conducting a SWOT analysis and a grounded theory approach, an explanation was found regarding the strategies needed to provide the best service for the implementation of regional development planning. Based on the results of the study, 14 coding forms 11 categories and simplified into 3 themes with a total score of 25. The highest score for coding is the service theme. It takes the right strategy in implementing regional development planning services in order to produce quality plans. From this grounded theory approach a new understanding can be found that "To produce quality planning documents, Bappeda needs to provide services in terms of planning to Regional Apparatuses related to equalization of perceptions in carrying out each planning process", because this creates opportunities and strengths from the Bappeda organization that is utilized to carry out regional development planning services in order to produce higher quality plans